Continuidade de políticas públicas em transições governamentais: o caso da política pública de saúde em Minas Gerais - Rodrigues, Raphael Vasconcelos Amaral (2018)
The continuity of public policies is a recurring theme in popular discussions, especially in electoral periods. Each government transition brings with it the expectation of change, but also the anguish of discontinuance in government public policies, and the democratic principle of alternation in power ensures that there is always the possibility of something new to emerge, bringing new airs to the public sector. The main objective of this work is to understand how the continuity of public policies in governmental transitions takes place, having as empirical reality the last three Planos Plurianuais de Ações Governamentais (PPAG) of the Secretaria de Estado de Saúde de Minas Gerais. For this purpose, a bibliographical review is developed with regard mainly to public policies and government transition, and the degree of continuity of the public health policy in Brazil is analyzed through a set of parameters of the defined government programs, considering the changes brought by the PPAGs of 2008-2011, 2012-2015 and 2016-2019. The transitions analyzed comprehend a period in which the same governor was re-elected, representing party maintenance, and a moment in which the opposition political group emerged victorious. Thus, the case study carried out in this work allows to conclude, based on the parameters used, that there is greater continuity in the public health policy in Minas Gerais when it comes to governmental transitions involving the same party than in moments in which the opposition is the winner of the electoral process.